Sphingolipids in human synovial fluid : a lipidomic study - Kosinska, Marta Krystyna; Liebisch, Gerhard; Lochnit, Guenter; Wilhelm, Jochen; Klein, Heiko; Kaesser, Ulrich; Lasczkowski, Gabriele; Rickert, Markus; Schmitz, Gerd; Steinmeyer, Juergen; Justus Liebig University Giessen (My University, 2014)
Articular synovial fluid (SF) is a complex mixture of components that regulate nutrition, communication, shock absorption, and lubrication. Alterations in its composition can be pathogenic. This lipidomic investigation aims to quantify the composition of sphingolipids (sphingomyelins, ceramides, and hexosyl- and dihexosylceramides) and minor glycerophospholipid species, including (lyso)phosphatidic acid, (lyso)phosphatidylglycerol, and bis(monoacylglycero)phosphate species, in the SF of knee joints from unaffected controls and from patients with early (eOA) and late (lOA) stages of osteoarthritis (OA), and rheumatoid arthritis (RA). SF without cells and cellular debris from 9 postmortem donors (control), 18 RA, 17 eOA, and 13 lOA patients were extracted to measure lipid species using electrospray ionization tandem mass spectrometry - directly or coupled with hydrophilic interaction liquid chromatography. We provide a novel, detailed overview of sphingolipid and minor glycerophospholipid species in human SF. A total of 41, 48, and 50 lipid species were significantly increased in eOA, lOA, and RA SF, respectively when compared with normal SF. The level of 21 lipid species differed in eOA SF versus SF from lOA, an observation that can be used to develop biomarkers. Sphingolipids can alter synovial inflammation and the repair responses of damaged joints. Thus, our lipidomic study provides the foundation for studying the biosynthesis and function of lipid species in health and most prevalent joint diseases.
Keywords: ddc:610